Malaysian corporate web sites: An investigation of web characteristics - Mahmood, Rosli; Saad, Sazali; Ismail, Shahifol Arbi; Abdul Rahman, Azhar (Universiti Utara Malaysia, 2007)
Rapid development on web technologies provides alternative mediums of marketing and maintaining good corporate relations among companies.However, web-based communication requires companies to carefully consider type of information to communicate and the format of presenting the information.This study examines the current state of Malaysian corporate web sites.Specifically, this study investigates the extent of information disclosure (content) and application of features (design) on web communication activities across listing boards and industrial sectors. 384 web sites of companies were examined using a coded checklist.The findings indicated that web site was heavily used by companies as a means of communicating corporate profile, contact information, and product information while adoptions rate of most web features were relatively low. Secondly, information intensive sectors were found to have greater motivation to establish web sites than product-based sectors.In most cases, web sites of main board companies were found to have richer contents and applied more web features.Overall, the results of the study provide evidence that industrial sector and listing board status of companies do influence the extent of information disclosure and adoption rate of web design among Malaysian companies.